Taking up the Cairo challenge : country studies in Asia-Pacific - Asian-Pacific Resource and Research Centre for Women (Kuala Lumpur : Asian-Pacific Resource & Research Centre for Women, 1999)
Review of the implementation of the ICPD Programme of Action after post-Cairo challenges to secure women's health, rights, and to promote gender equality.
Keywords: Women's rights -- Asia; Women's rights -- Pacific Area; Women -- Health and hygiene -- Asia; Women -- Health and hygiene -- Pacific Area; Reproductive health -- Asia; Reproductive health -- Pacific Area